2019
DOI: 10.3390/molecules24071420
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects on Thrombin of Paris Saponins and In Vivo Hemostatic Activity Evaluation of Paris fargesii var. brevipetala

Abstract: The resource shortage of Rhizoma Paridis has never been effectively addressed, and the industry continues to search for alternative resources. The in vitro effects on thrombin of Paris saponins and in vivo hemostatic activity of Paris fargesii var. brevipetala (PF) were evaluated in this study. PF is considered to be an alternative source of Rhizoma Paridis (RP). The in vitro incubation experiment was designed to investigate the effects on thrombin activity of Paris saponin H (PS H) and saponin extract in PF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…However, Paris fargesii Franch is a sibling species of P. polyphylla var. yunnanensis and has a high saponin content (Wen et al, 2019). Therefore, it is important to isolate and identify symbiotic strains from P. fargesii Franch and screen them for the growth and accumulation of saponins to improve the growth rate of P. fargesii Franch.…”
Section: Introductionmentioning
confidence: 99%
“…However, Paris fargesii Franch is a sibling species of P. polyphylla var. yunnanensis and has a high saponin content (Wen et al, 2019). Therefore, it is important to isolate and identify symbiotic strains from P. fargesii Franch and screen them for the growth and accumulation of saponins to improve the growth rate of P. fargesii Franch.…”
Section: Introductionmentioning
confidence: 99%
“…In additional, CCl4-induced hepatic fibrosis were significantly improved by polyphyllin D, polyphyllin G, polyphyllin VI, and formosanin C ( Man et al, 2014a ; Hong et al, 2016 ; Han et al, 2019 ). The mouse tail snipping model demonstrated that Paris saponin H, polyphyllin I, polyphyllin II, and polyphyllin VII could serve as favorable hemostatic agents ( Sun et al, 2014 ; Wen et al, 2019 ; Qiao et al, 2021 ). Polyphyllin V and polyphyllin VII showed powerful antibacterial activity against propionibacterium acnes ( Qin et al, 2012 ).…”
Section: Methods and Strategiesmentioning
confidence: 99%
“…According to a previous study, polyphyllin E inhibits ovarian cancer cells by downregulating the AKT/NF-κB pathway, reducing the expression of MMP2 and MMP9, and inhibiting the proliferation, migration, and invasion of ovarian cancer cells, thereby achieving an inhibitory effect in ovarian cancer cells (Liu Y. et al, 2022). In another study, polyphyllin H inhibited the growth of hepatoma cells and xenografts by suppressing the Wnt/β-catenin pathway, while knocking out of the β-catenin gene significantly inhibited this phenomenon (Chen T. et al, 2019). In addition, polyphyllin H-treated U251 human glioma cells had upregulated P21 and P27 expression and downregulated cyclin D expression, which further induced cell cycle arrest of U251 cells at the G1 phase.…”
Section: Antitumor Effects Of Other Active Ingredients In Rhizoma Par...mentioning
confidence: 96%
“…us, it has been widely used as a hemostatic medicine in China. A recent study demonstrated that Paris saponin H significantly enhanced thrombin activity, thereby shortening the bleeding time in the mouse tail snipping model, suggesting that Paris saponins could interact with thrombin [54]. Polyphyllin VII was found to act directly on platelets and hemostasis and cause 62% platelet aggregation at 300 ug/ml concentration [11].…”
Section: Antifibrosismentioning
confidence: 99%